Covalent conjugation of mechanically stiff graphene oxide flakes to three-dimensional collagen scaffolds for osteogenic differentiation of human mesenchymal stem cells. (March 2015) - Kang, Seokyung; Park, Jong Bo; Lee, Tae-Jin; Ryu, Seungmi; Bhang, Suk Ho; La, Wan-Geun; Noh, Myung-Kyung; Hong, Byung Hee; Kim, Byung-Soo
Abstract: Mesenchymal stem cells (MSCs) preferentially differentiate to osteogenic lineage when cultured on mechanically stiff substrates. However, collagen sponges, clinically approved scaffolds for bone regeneration, provide soft microenvironment to MSCs. Here, we demonstrate that the covalent conjugation of mechanically stiff graphene oxide (GO) flakes to three-dimensional (3D) collagen scaffolds improves the mechanical properties of the scaffolds and promotes the osteogenic differentiation of human MSCs (hMSCs) cultured on the scaffolds. The covalent conjugation of GO flakes to collagen scaffolds increased the scaffold stiffness by 3-fold and did not cause cytotoxicity. hMSCs cultured on the GO-collagen scaffolds demonstrated significantly enhanced osteogenic differentiation compared to cells cultured on non-modified collagen scaffolds. The enhanced osteogenic differentiation observed on the stiffer scaffolds was likely mediated by MSC mechanosensing because molecules that are involved in cell adhesion to stiff substrates were either up-regulated or activated. The 3D GO-collagen scaffolds could offer a powerful platform for stem cell research and orthopedic regenerative medicine.